2012
DOI: 10.1002/cnm.2518
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical responses of a pig head under blast loading: a computational simulation

Abstract: A series of computational studies were performed to investigate the biomechanical responses of the pig head under a specific shock tube environment. A finite element model of the head of a 50-kg Yorkshire pig was developed with sufficient details, based on the Lagrangian formulation, and a shock tube model was developed using the multimaterial arbitrary Lagrangian-Eulerian (MMALE) approach. These two models were integrated and a fluid/solid coupling algorithm was used to simulate the interaction of the shock w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 34 publications
(64 reference statements)
1
37
0
Order By: Relevance
“…In other words, the solid and fluid elements coexisted in the same space. The fluidsolid interaction (FSI) parameters used in this study were consistent with those in the study by Zhu et al 13,14 A parametric study was conducted on the number of coupling points (1, 2, and 3), and it has been revealed that the coupling points had little effect on the results. Therefore, to save computational cost, one coupling point was used.…”
Section: Blunt Impactmentioning
confidence: 83%
“…In other words, the solid and fluid elements coexisted in the same space. The fluidsolid interaction (FSI) parameters used in this study were consistent with those in the study by Zhu et al 13,14 A parametric study was conducted on the number of coupling points (1, 2, and 3), and it has been revealed that the coupling points had little effect on the results. Therefore, to save computational cost, one coupling point was used.…”
Section: Blunt Impactmentioning
confidence: 83%
“…Species include rodents [109,128,135,138,140,143,144,[161][162][163][164][165][166][167], pigs [168][169][170][171][172][173], and sheep [174][175][176]. These experimental models offered a measure that human physical models and human surrogate tests often could not provide-an estimate of the injuries that occurred throughout the brain as a result of the mechanical loading.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…In the displacement-input simulations (e.g., from compression of the skull), less than 1% nominal strain at different rates was applied with a smooth prole that resulted in peak accelerations below and above the critical acceleration. In the pressure-input simulations (e.g., pressure wave passing through the scalp and skull), pressure pro- files reported in [22] for rat brain were selected as the basis and the peak pressure was scaled based on blast injuries reported in pigs [23]. Clearly for future studies directly measured boundary conditions that result in various degrees of BINT are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the second set of simulations, based on the experimental pressure measurements in a rat BINT model with BOP generated from a shock tube and pressures measured in the third ventricle [22], two pressure pro les were scaled and applied to the model. The scaling factor of the two pressure pro les were determined to give initial peak pressures ( p max ) according to the lower end (50 kPa) and mid-range (200 kPa) of the eld measurements pertaining to blast induced brain injury as a result of blast explosions [23]. …”
Section: Discontinuous Galerkin (Dg) Finite Element Modelmentioning
confidence: 99%